(untitled) (Research, Society and Development, 2022)
The population aging process and the changes in the sexual behavior of the elderly population, through methods to circumvent sexual dysfunctions, along with a resistance to use condoms have generated a new epidemiological scenario about sexually transmitted infections in the elderly in recent years, which is notable with the increase in the number of cases. The goal is to identify the prevalence of STI cases, in Brazil, in female and male individuals aged 60 years or older. This is a cross-sectional, observational, and quantitative study made by consulting SISAB, which data was obtained and analyzed for the period from 2017 to 2021, which were subsequently rearranged using the Microsoft Excel program. In this period, a total of 275,380 cases of sexually transmitted infections were reported in the elderly population between 60 and 89 years old. It is noticeable the growth of cases from 2017 to 2019, a major drop in 2020 and a growth in 2021. The highest reporting category was the female one. It is concluded that STIs in the elderly is a public health problem surrounded by challenges that need to be improved, for instance, through the implementation of specific prevention campaigns, considering the needs and particularities of this social group.